Management of Maize Lethal Necrosis (MLN) in Tanzania - Selian Agriculture Research Institute; International Center for Tropical Agriculture (International Food Policy Research Institute, 2017)
This study contains data about mapping prevalence, incidence, and severity of MLN in northern Tanzania. Project title: Integrated Approaches to Manage Maize Lethal Necrosis (MLN) Disease in Tanzania Project abstract: Mapping prevalence, incidence and severity of MLN in northern Tanzania. Project website: http://africa-rising.net